2018
DOI: 10.1002/jbm.b.34217
|View full text |Cite
|
Sign up to set email alerts
|

Ionic cobalt but not metal particles induces ROS generation in immune cells in vitro

Abstract: Total joint replacement is one of the most successful procedures in orthopedic surgery today. However, metal implant materials undergo wear and corrosion processes. Generated particles and ions can cause a variety of cellular reactions. Cobaltcontaining alloys are used frequently in implant materials. Some studies suggest that cobalt exhibits potential cytotoxic effects, for example, via generation of reactive oxygen species (ROS). To further elucidate the effects of cobalt on human cells, we determined cell v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 57 publications
0
23
0
1
Order By: Relevance
“…However, in contrast with the inflammatory reaction results in our murine model, some in vitro studies have shown different results. Chamaon et al indicated that the treatment of a human monocytic cell line with ionic cobalt led to a decrease in metabolic activity [Water Soluble Tetrazolium-1(WST-1) assay], while CoCrMo particles had no effect [47]. They explained that the rather large abrasive particles (from 200 nm to several micrometers) used in their study might have resulted in the relatively low impact of CoCrMo particles [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast with the inflammatory reaction results in our murine model, some in vitro studies have shown different results. Chamaon et al indicated that the treatment of a human monocytic cell line with ionic cobalt led to a decrease in metabolic activity [Water Soluble Tetrazolium-1(WST-1) assay], while CoCrMo particles had no effect [47]. They explained that the rather large abrasive particles (from 200 nm to several micrometers) used in their study might have resulted in the relatively low impact of CoCrMo particles [47].…”
Section: Discussionmentioning
confidence: 99%
“…Chamaon et al indicated that the treatment of a human monocytic cell line with ionic cobalt led to a decrease in metabolic activity [Water Soluble Tetrazolium-1(WST-1) assay], while CoCrMo particles had no effect [47]. They explained that the rather large abrasive particles (from 200 nm to several micrometers) used in their study might have resulted in the relatively low impact of CoCrMo particles [47]. Because particle size is considered a critical parameter that influences the biological reactions to wear particles, the majority of MoM-produced particles are usually from 40 to 60 nm [2,48].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed model of bi-directional, cyclic crosstalk between the gut microbiome and implant microenvironment. Arthrofibrosis, as discussed in the text, may be a contributing factor stress, 95 and contribute directly to alterations in the gut microbiome. 96,97 Cobalt ions are known to be absorbed by the human small intestine when ingested.…”
Section: F I G U R Ementioning
confidence: 97%
“…The authors highlighted that toxic effects of cobalt dichloride depended on a dose and a time period during which cells were exposed to a medium containing heavy metal ions. It was reported that cobalt dichloride was able to induce the formation of a superoxide anion in the mitochondria of various human cells [27].…”
mentioning
confidence: 99%